Photocatalytic Properties and Plastic Degradation of TiO2 Nanocomposite with Synthetic-rutile from Natural Ore - Wanichaya MEKPRASART; Titarat THONGPRADITH; Wisanu PECHARAPA; Keiichi N. ISHIHARA (My University, 2018)
Titanium dioxide (TiO2) is considered a main material in energy and environment fields. This work focused on the production of synthetic rutile-TiO2 (LA) material from natural ore by milling-ultra sonic assisted in acid treatment. Modified-TiO2 nanocomposite of synthetic rutile and anatase nanopowder was synthesized by high energy milling process. After milling process, the average sizes of samples were decreased at 30% as calculated from XRD peaks. The band gap value of samples analyzed by UV-Vis spectrometer showed that the decrease of the band gap in LA composite at 3.34 eV might be associated with the presence of rutile phase in anatase matrix relating to the highest photocatalytic activity under visible light illumination. Polyethylene plastic was supplemented with different LA nanocomposite loading by thermal attachment process. Photocatalyst property of LA nanocomposite was investigated photocatalytic activity under Xe lamp illumination and investigated by FTIR and XRD technique. The optimized content of LA nanocomposite was performed at 2 wt.% in PE film. FTIR patterns did not detect the difference of plastic degradation. However, the significant change in PE crystalline monitored by XRD technique confirmed the decrease of crystallite size by peak shifted position and size decreasing at 10% by photocatalyst effect.
Keywords: Rutile; Degradation; TiO2 Photocatalysis and Solar Cells